KETERKAITAN VARIASI PRODUK DAN TENAGA KERJA TERHADAP PENINGKATAN LABA BENGKEL AHAS PANDAAN - syairozi, muhamad (Universitas Muhammadiyah Yogyakarta, 2019)
This study was intended to identify the effect of variations in product and labor to increase profits at AHASS Workshop Pandaan whether theyhave a partial effect, where the variables simultaneously and more dominant, type of quantitative research conducted by validity test research methods, reliabillity, classical assumption, regression, coefficient of determination, t-test and f test. Methods of data collection were done by observation, questionnaire and documentation. From the results of the above data it can be concluded the data is valid, and there is a relationship reliable partially and simultaneously, and the most dominant variable is a variation of products. From the results of multiple linear regression that affects predominantly to the increase in earnings in the AHASS Workhop Pandaan was a variation of products. Product Variations regression coefficient (X1) of 0.563 means that if variations product increased by one unit then the earnings will increase by 0.563 assuming that other variables held constant influence.Keywords: product variations, labor and increasing profit